Biological foundations of optimization of training loads of athletes - Mintszyunke Shan,; Kozhedub M.S. ,; Vrublevskiy E.P. , (Theory and Practice of Physical Culture, 2024)
Abstract Objective of the study was to consisted in studying the main approaches of the coaches of Belarus and China to taking into account the biorhythmological characteristics of the athletes' body when planning their training process and determining the dynamics of the manifestation of speed and strength abilities during the OMC among athletes specializing in various sports. Methods and structure of the study. A questionnaire was developed and a survey was conducted of coaches (n=16) involved in the training of track and field athletes in the Republic of Belarus and specialists (n=12) who train hockey players in China. Also, to determine the well-being, changes in mental state, performance, tolerance of training and competitive loads in various phases of the body's biorhythmics, a survey and testing of 18 qualified Belarusian runners at various distances and 23 Chinese female athletes involved in hockey were conducted. Results and conclusions. Analyzing the data of the coaches' questionnaire, it can be stated that most specialists, when planning the training process, do not take into account the phase of the ovarian-menstrual cycle of athletes, which negatively affects the tolerability of the proposed loads, the functional state and well-being of girls. The results of the survey and the results of testing of athletes indicate the presence of significant phase changes in the indicators of motor abilities of runners and hockey players in each of the phases of the OMC.